THE INFLUENCE OF INFORMATION SOURCES TOWARD KNOWLEDGE, ATTITUDE, AND STUDENT ACTION UNDER COVID-19 - Dewi Rokhmah; Khoiron Khoiron; F K Alfarisy; Nafi'atul Irbah (UNEJ e-Proceeding, 2023)
Background: This purpose of this research is to determine the effect of Covid-19 information sources on student’s knowledge, attitudes and actions. Methods: This research is Quantitative research and used cross-sectional method with Google Form questionnaire. Respondents were 303 active students in some universities in Indonesia. The variable independent of this study is the Covid-19 information source, which can be identified by providing several sources of information received by respondents. The variable dependent of this study are knowledge, attitudes, and actions. Data collected was analysed using Structural Equation Modelling (SEM) analysis on IBM® SPSS AMOS version 23.0. Results: The result of this research is social media has the highest value of information access ease of all information source options provided with a percentage of 97% of the total 303 respondents, then the source of information from the government with a percentage of 93.7% and information sources from tv 86.1%. The value (P) explains the influence of social media on significant student knowledge. Estimate explains the weight of influence (Regression Weights) where social media negatively affects the level of student knowledge. Grades (P) also explains the effect of government information knowledge significant student. Estimate explains the weight of influence (Regression Weights) where government information has a positive effect on the level of student knowledge. The value (P) explains the influence of attitude towards student actions significantly. Estimate explains the weight of influence (Regression Weights) where attitudes have a positive effect on the level of student action. The most accessible source of information is social media. Conclusions: Social media information sources have a negative effect on the level of student knowledge. Government information sources have a positive effect on the level of student knowledge. Attitude has a positive effect on student actions. it needed that student’s collage are expected to be able to access information about Covid-19 through the official website provided by the government.